IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 78 TAHUN 2015 TENTANG PENGUPAHAN MENGENAI PERAN DEWAN PENGUPAHAN KOTA SURABAYA DALAM MENENTUKAN UPAH MINIMUM KOTA SURABAYA - ALFAN SYAHPUTRA, HELMY; NUGROHO, ARINTO (NOVUM : JURNAL HUKUM, 2019)
Abstrak Berlakunya Peraturan Pemerintah nomor 78 tahun 2015 tentang Pengupahan (PP Pengupahan) menimbulkan berbagai dampak, salah satunya tentang penggunaan formula dalam penetapan Upah Minimum Kota (UMK) Surabaya sehingga beberapa pihak yang khawatir bahwa PP Pengupahan akan menghilangkan peran dari Dewan Pengupahan Kota Surabaya dalam menentukan UMK Surabaya yang akan merugikan pekerja di Kota Surabaya. Tujuan dari penelitian ini adalah mengetahui implementasi peran Dewan Pengupahan Kota (Depeko) Surabaya dan Proses penetapan UMK Surabaya setelah berlakunya PP Pengupahan. Penelitian berjenis penelitian yuridis sosiologis, melalui teknik wawancara dan observasi. Informan dari pihak Dewan Pengupahan Kota Surabaya dan juga pihak Serikat Pekerja Kota Surabaya dengan menggunakan metode deskriptif, artinya peneliti akan memberikan sebuah pemaparan secara faktual atas hasil penelitiannya. Hasil penelitian menunjukkan bahwa berlakunya PP Pengupahan mempermudah kinerja Depeko Surabaya dalam memberikan usulan UMK Surabaya kepada Walikota Surabaya. Kalau sebelum keluar PP Pengupahan, penentuan UMK Surabaya harus melalui tahapan panjang, setelah keluar PP Pengupahan, proses tersebut dapat dipersingkat melalui survei Komponen Hidup Layak (KHL) yang awalnya 1 tahun sekali menjadi 5 tahun sekali dan menggunakan formula yang telah ditentukan di PP Pengupahan. Proses penetapan UMK Surabaya setelah keluarnya PP Pengupahan tidak berbeda dari Proses sebelum berlakunya PP Pengupahan. Perbedaan hanya ada pada proses penggunaan survei KHL sebagai acuan penetapan UMK Surabaya yang diganti dengan formula pada PP Pengupahan. Kata kunci : Peran Dewan Pengupahan kota Surabaya, Penetapan UMK Surabaya, Peraturan Pemerintah Nomor 78 tahun 2015 tentang Pengupahan Abstract The enactment of the Government Regulation number 78 of 2015 concerning Wages have various impacts, one of them is that using of formulas in the determination of the Surabaya minimum wages so that parties are concerned that the Government Regulation number 78 of 2015 Preliminary will eliminate the role of the Surabaya`s City Wage Council in determining Surabaya Minimum Wages. The aims of the study are to Know the Implementation difference of role of the Surabaya city wages council after the enactment of the government regulation number 78 of 2015 concerning wages and to know the process determination Surabaya minimum wages after the enactment of that regulation.This research was using sociological juridical research with the techniques of the interview and observation. The informants of the interview were from the Surabaya City Wage Board and the Surabaya City Workers Union. The results of the interview of the four informants were analyzed by using the descriptive method. That means the researcher give a presentation in factual on the results of his research. The results of the study explained that the Applicability of the Government Regulation number 78 of 2015 concerning Wages made it easier for the Surabaya`s City Wage council to provide Surabaya Minimum wages proposal to the Mayor of Surabaya. Before the regulation, the determination of the Surabaya minimum wages must go through a long stage, after issuing that regulation, the process can be shortened through a survey of Decent Living Components which initially once a year becomes 5 years and uses the formula specified in of the Government Regulation number 78 of 2015 concerning Wages. The process of determining the Minimum wages of Surabaya after the issuance of the of the Government Regulation number 78 of 2015 concerning Wages is not different from the Process before the enactment of the Wages PP. The difference is only in the process of using the Decent Living Components survey as a reference for determining the Surabaya Minimum wages which is replaced with a formula that was placed in the Government Regulation number 78 of 2015 concerning Wages. Keywords : The Role of the Surabaya`s city wages council, Determination of the Surabaya Minimum wages. the Government Regulation number 78 of 2015 concerning Wages.